A Case of Tophaceous Pseudogout on 18F-FDG PET/CT Imaging. (February 2019) - Shen, Guohua; Su, Minggang; Liu, Bin; Kuang, Anren
Abstract : Abstract: A 53-year-old man with a 10-year history of gout was admitted to our hospital due to chronic low back pain. Initial CT examinations showed a high-density mass with bone destruction of bilateral facet joints at the L3 to L5 level. MRI findings also revealed lesion with the dural sac compression. On PET/CT, the juxta-articular mass of bilateral L3 to L5 facet joints showed abnormal FDG uptake with an SUVmax of 4.2. The possible diagnosis may be gouty tophi; however, the biopsy revealed the diagnosis of calcium pyrophosphate dihydrate deposition disease, also referred to as pseudogout.